Seedling growth and survival of five tree species in secondary forests and adjacent pastures in the montane rain forests of Southern Costa Rica - Ley-López, Juan Manuel (2016)
Successful forest restoration in tropical environments is limited by the paucity of studies on the initial establishment and early survival requirements of seedlings of most native tropical tree species under disturbed conditions. Here, we evaluated the initial growth responses and the regeneration potential of seedlings of five tree species native to Costa Rica (Hasseltia floribunda, Inga densiflora, Persea americana, Tapirira mexicana and Trichilia pittieri). Seedlings were grown in secondary forests and adjacent open pastures under contrasting conditions of light availability. We quantified seedling growth, survival and herbivory from August 2010 to August 2011 on a monthly basis, and measured differences in leaf mass per area (LMA) at the end of the experiment. We found significant variation in growth responses between the understory of secondary forests and pastures. Growth in height was highest in pastures across all species, with I. densiflora, P. americana and T. mexicana showing the most striking differences. In contrast, H. floribunda and T. pittieri did not show differences in diameter growth between environments. Except for T. mexicana, herbivory increased throughout the experiment in all the species. Herbivory increased faster in pastures for H. floribunda and T. pittieri and showed higher rates in the forest understory for I. densiflora and P. americana. Seedling survival showed significant differences for all species across environments. Survival of H. floribunda and I. densiflora was higher in secondary forests, whereas the other species showed higher survival in pastures. Leaf mass per area showed higher values in the pastures across all species, it suggests that individuals exposed to high light conditions had great photosynthetic rate and great leaf construction capacity. Due to their rapid growth and high survival, I. densiflora and T. mexicana showed great potential to restore abandoned pastures and secondary forests. Increasing our knowledge on the response of seedlings under disturbed conditions in tropical ecosystems is critical for improving the restoration of altered environments by matching the ecological amplitude of native species with specific environmental conditions.